2011
DOI: 10.1002/jobm.201000327
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐dependent and ‐independent molecular analysis of the bacterial community within uranium ore

Abstract: The bacterial community structure within a uranium ore was investigated using culture-dependent and -independent clone library analysis and denaturing gradient gel electrophoresis of 16S rRNA genes. The major aerobic heterotrophic bacteria were isolated and identified, and their resistance to uranium and other heavy metals was characterized. Together with near neutral pH, moderate organic carbon content, elevated U and other heavy metals (V, Ni, Mn, Cu, etc.), the ore showed high microbial counts and phylotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 33 publications
2
16
1
2
Order By: Relevance
“…Physiochemical parameters including pH, conductivity/salinity of the samples were measured by an Orion star™ series meter (Thermo Electron Corporation) following the procedure as described elsewhere (Islam and Sar 2011a). Heavy metals and actinide elements were estimated by ICP-MS (Varian) and/or AAS (Perkin-Elmer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiochemical parameters including pH, conductivity/salinity of the samples were measured by an Orion star™ series meter (Thermo Electron Corporation) following the procedure as described elsewhere (Islam and Sar 2011a). Heavy metals and actinide elements were estimated by ICP-MS (Varian) and/or AAS (Perkin-Elmer).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Rastogi et al (2010) has reported abundance of Proteobacteria , Acidobacteria and Bacteriodetes in a U mine impacted site in USA. Studies conducted in our laboratory have revealed microbial communities within two U mines (Jaduguda and Banduhurang) along with potential of inhabitant bacteria in U and other metal resistance and sequestration and impact of U ore contamination on soil microbial diversity (Sar et al 2007; Choudhary and Sar 2011; Islam et al 2011; Islam and Sar 2011a, b). With vast genetic and metabolic diversity, these microorganisms were found to interact with metals and radionuclides directly or indirectly by redox transfer, biosorption, bioaccumulation or bioprecipitation affecting their environmental mobility and toxicity (Suzuki and Banfield 2000; Tabak et al 2005; Nedelkova et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate these microflora, several methods, such as the culture-based assay, denaturing gradient gel electrophoresis (DGGE) and next generation sequencing (NGS)-based metagenomics, have been applied (Handelsman, 2004;Hong et al, 2011;Islam and Sar, 2011;Shokralla et al, 2012;Streit and Schmitz, 2004;Zhalnina et al, 2012). The culturebased assay has limitation in terms of the study of unculturable microbes from environmental samples, such as soil.…”
Section: Full Papermentioning
confidence: 99%
“…일반적으로 미생물상을 연구하기 위한 방법으로, 배양기반 어세이(culture-based assay)와 변성구배전기영동(denaturing gradient gel electrophoresis, DGGE)기법이 이용되고 있다 [7,10,14]. 배양기반 어세이는 목적 미생물을 분리․배양하여 실 험할 수 있는 장점이 있으나, 현재까지 배양가능한 미생물은 전지구상 미생물의 0.02%를 차지하는 것으로 추측되며, 나머 지 99.8%의 미생물중 대부분의 미생물은 배양성 또는 난배양 성으로 정확하게 분류되고 있지 않은 실정이다 [2,22].…”
unclassified
“…배양기반 어세이는 목적 미생물을 분리․배양하여 실 험할 수 있는 장점이 있으나, 현재까지 배양가능한 미생물은 전지구상 미생물의 0.02%를 차지하는 것으로 추측되며, 나머 지 99.8%의 미생물중 대부분의 미생물은 배양성 또는 난배양 성으로 정확하게 분류되고 있지 않은 실정이다 [2,22]. 변성구 배전기영동기법은 환경시료로부터 난배양성 미생물상 분석 이 가능한 장점이 있으나, 대규모의 16S rRNA 염기서열을 획 득하기에는 제한적이다 [10]. 따라서 차세대 시퀀싱(next generation sequencing, NGS)을 기반으로한 메타지노믹스(metagenomics)기법은, 환경시료로부터 대규모 미생물상 분석 및 배양성․난배양성 미생물 군집분석에 매우 적합한 방법으로 알려져 있다 [7,21].…”
unclassified